Phylogenetic relationships in two African Cedreloideae tree genera (Meliaceae) reveal multiple rain/dry forest transitions - (:unkn) unknown (My University, 2019)
Resolving phylogenetic relationships allows the investigation of how species diversity has evolved in various ecosystems. The genera Entandrophragma and Khaya consist of tree species distributed in different African biomes (lowland rain forest, dry forest and savanna, montane forest), and are suitable to examine how (single or multiple events) and when the processes of diversification led to biome transitions. Based on the sequencing of plastome (pDNA: c. 160,000 bp), ribosomal DNA (rDNA: c. 5300 bp), and habitat characteristic data for each species, we have: (i) reconstructed phylogenetic relationships between species and estimated the divergence period between the main lineages, and (ii) reconstructed ancestral states regarding biome preferences. The phylogenetic trees obtained with both markers support monophyly of the five sections of Entandrophragma previously defined based on fruit and floral characters. Nevertheless, the position of some species from the pDNA and rDNA tree topologies varied within sections. In Khaya, pDNA and rDNA show very divergent topologies, possibly due to a more recent diversification involving incomplete lineage sorting and/or recurrent hybridization events. Khaya diversified during the Pliocene and Pleistocene according to both markers; whereas, according to rDNA data, the Entandrophragma sections diverged during the early Miocene and species within sections diverged from the late Miocene to the Pleistocene. Divergence date estimates tended to be more recent using pDNA data. Biome transitions could not be reconstructed in Khaya as the species tree remains unresolved. Contrarily, three independent biome transitions were inferred in Entandrophragma. The first transition from rain to dry forests occurred during the Miocene and two other transitions were inferred during the Pleistocene, one from rain forest to dry forest and another from rain forest to mountain forest. Overall, we demonstrate that multiple biome transitions
Keywords: African Research